Relaxin-2 in Cardiometabolic Diseases: Mechanisms of Action and Future Perspectives - Feijóo-Bandín, Sandra; Aragón-Herrera, Alana; Rodríguez-Penas, Diego; Portolés, Manuel; Roselló-Lletí, Esther; Rivera, Miguel; González-Juanatey, José R.; Lago, Francisca (Frontiers in Physiology, 2017)
Despite the great effort of the medical community during the last decades, cardiovascular diseases remain the leading cause of death worldwide, increasing their prevalence every year mainly due to our new way of life. In the last years, the study of new hormones implicated in the regulation of energy metabolism and inflammation, especially adipokines, has raised a great interest among the scientific community regarding their implications in the development of cardiometabolic diseases. In this review, we will summarize the main actions of relaxin, a pleiotropic hormone that was previously probed to improve acute heart failure and that participates in both metabolism and inflammation regulation at cardiovascular level, and will discuss its potential as future therapeutic target to prevent/reduce cardiovascular diseases.